The description of a new brackish water ciliate species from China, Trachelostyla aestuarina n. sp., with a species key and biogeographic investigation for Trachelostyla (Ciliophora, Sporadotrichida) - Zhang, Zihui; Hines, Hunter N.; Pan, Hongbo; Jiang, Jiamei (Frontiers in Marine Science, 2022)
The ciliated protists are a diverse group of microbial eukaryotes that play an important role in the functioning of microbial food webs. The genus Trachelostyla Borror, 1972 is is a small group of hypotrich ciliate comprised a few species that is awith a non-twisted distinctly cephalized cellbodyshape. The overall taxonomy has been challenging for this group and the understanding of their diversity and distribution is therefore relatively limited. To further investigate this group, we report here on two species from the East China Sea, Trachelostyla aestuarina n. sp. and T. caudata Borror, 1972, including their in vivo morphology, infraciliature, and phylogenetic relationships based on 18S rRNA gene sequences. The physiological reorganization stages of the latter are also investigated. Trachelostyla aestuarina is characterized by a combination of features including a bipartite cell shape, a size of 150–216 220 × 1615–31 35 μm, scattered cortical granules and multiple macronuclear nodules (37–55). Trachelostyla caudata has only ten cirri in the frontal region, less than its congeners, and thus we improvedrevised the definition of the genus. The global distribution of Trachelostyla is summarized based on the available literature, and a key to the valid species are is provided. This work improves the overall knowledge of hypotrich biodiversity and provides underpinning for future researchers in global regions for environmental monitoring and resource investigations.